Sumur Amber Blitar Solusi Universal - Ikmah, Amit Dana; Islam, Muhammad Thoriqul; Al-Am, Maftah Rozani; Neni, Titin Erviana Ayu; Qardhawi, Muhammad Yusuf (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
In the middle global ecological and spiritual crisis, ”Sumur Amber” in Blitar offers solutions based on local wisdom. The research methodology used a qualitative approach with an ethnographic research type. Data were collected through participant observation and in-depth interviews with key informants in several villages in Blitar Regency. Data analysis used the interactive model of Miles, Huberman, and Saldana to explore the contribution of the “Sumur Amber” to global harmony. The results show three dimensions of universal wisdom: ecological (traditional water conservation), spiritual (human-nature balance), and socio-cultural (mutual cooperation). As many as 87% of tourists experience a transformation beyond conventional tourism. The philosophy of